Magnetic properties of dolerite dykes and lamprophyre sills from Jharia coal fields, Damodar valley basin, India - Nishad, Ramesh K.; Sinha, Anup K.; Kumaravel, V.; Patil, S. K. (My University, 2013)
The Gondwana (Early Permian to Early Cretaceous) basins of eastern India have been intruded by ultramafic-ultrapotassic and mafic (dolerite) dykes. Total 35 samples from 7 sites of dolerite dykes and lamprophyre sills have been collected from the Jharia coal field of the Damodar valley basin for rock magnetic studies. The investigations mainly comprise of magnetic susceptibility measurement, isothermal remanent magnetization (IRM), Lowrie-Fuller (L-F) test and thermomagnetic (K-T) experiment. The natural remanent magnetization (NRM) intensities measured on 450 specimens of dolerite dykes and lamprophyre sills show a mean value of 4.06 A/m and 0.003 A/m. Magnetic susceptibility values indicate mean values of 30.93 x 10-3 and 0.41 x 10-3 SI units. The Koenigsberger ratio (Qn) value of dykes and sills show mean value of 3.47 and 0.19, respectively. Rock magnetic studies indicate that titano-magnetite/ magnetite of pseudo single domain (PSD)/ single domain (SD) type are the main magnetic minerals present in the studied samples of the Damodar valley basin.
Keywords: Damodar valley basin; Dolerite dykes; Lamprophyre sills